Study of Challenges and Opportunities in Northern India’s Growth of the Medicinal Plant Sector (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The study goals were to Study of challenges and opportunities in Northern India's growth of the medicinal plant sector. The survey reveals that there is a rich diversity of significant medicinal plants in northern India, and attempts are being made at various levels to utilize this resource to build up the medicinal plant sector.